Are the market indexes efficient portfolios? The Spanish case of IBEX-35 - González Sánchez, Mariano; Universidad CEU Cardenal Herrera (Pontificia Universidad Javeriana, 2014)
In financial management and asset pricing is often used the market as the efficient market portfolio. The empirical studies to test the efficiency of market index usually assume a gaussian behavior (mean-variance). By contrast, this paper proposed a backtesting methodology from the post type-I and II errors, for both gaussian and non-gaussian behavior. The results on Spanish market index (IBEX-35) show that optimal portfolios may be more efficient than the IBEX-35 with fewer assets, which under a non-Gaussian test are exceeded and, without exhibiting the usual problem of market risk premiums not positive.